Reproductive success of Whiskered Tern Chlidonias hybrida in eastern Spain in relation to water level variation - Ortiz Lledó,Álvaro; Vidal Mateo,Javier; Urios Moliner,Vicente (PeerJ, 2018)
Background A study on the Whiskered Tern Chlidonias hybrida was carried out between 2002 and 2009 in wetlands of eastern Spain to evaluate how water level fluctuation affects its reproductive success (hatching, fledgling and breeding success). This species is catalogued as Vulnerable in Spain and has an unfavorable conservation status in Europe. Methods Our study includes 18 sampling areas from five wetlands, covering a total of 663 nests, 1,618 eggs, 777 nestlings and 225 fledglings. The colonies were visited at least twice per week in breeding period. The number of eggs and/or nestlings present in each nest were annotated each time the colonies were visited with the aim to compare the evolution of these parameters with time. Hatching success was calculated as the proportion of egg that hatched successfully. Fledgling success and breeding success were calculated as the proportion of chicks that fledged successfully and the proportion of eggs that produced fledglings. We used the Kruskal–Wallis test to analyze the differences in the dependent variables hatching, fledgling and breeding success among the wetlands and the sampling areas. We explored the relationship between the different reproductive success with the average fluctuation rate and the anchoring depth of nests, using statistics of the linear regression. Results It was observed that the reproductive success varied significantly in the interaction among the different categories of water level fluctuation and the different areas (using the Kruskal–Wallis test). Our records showed that pronounced variations in water level destroyed several nests, which affected the Whiskered Tern reproductive success. Considering all events that occurred in 18 areas, the mean (±SD) of nests, eggs and nestlings that were lost after water level fluctuations were of 25.60 ± 21.79%, 32.06 ± 27.58% and 31.91 ± 21.28% respectively, also including the effects of rain and predation. Discussion Unfavorable climatic events, such as strong wind, rain or hail, also caused the loss of nests, eggs and nestlings, even when wetland water levels remained constant. The influence of the anchorage depth of the nest and the water level fluctuation rate were analyzed and did not provide statistically significant results. It was not possible to establish a clear pattern on these latter variables, so further studies are needed to obtain more significant results. We propose to undertake similar studies in wetlands where the water level can be regulated, with the range of nest anchorage depth on the emergent vegetation being between 30 and 60 cm, which could improve the reproductive success in this kind of habitats. As recommendation, in water level controlled wetlands (that use sluices), it should not vary more than ±6 cm in a short time (1–2 days) once the nests are established since it negatively affects their reproductive success.
Keywords: Migratory species; Reproductive success; Wetland; Water level fluctuation; Chlidonias hybrida; Whiskered Tern; Hatching success; Fledgling success